Challenges and Strategies of Health Human Resource Management in Addressing Global Changes in The Digital Era - Novitayanti Pongsapan; Andriyana Abdullah; Abdul David Pongsapan (International Journal of Health Engineering and Technology, 2026)
Digital transformation has become a strategic pillar in strengthening global health systems, particularly in improving service efficiency, quality, and accessibility. These changes demand adaptive and competent health human resources capable of responding to rapid technological advancements. This study aims to analyze the challenges and strategies of health human resource management in addressing global changes in the digital era. A literature review method was employed through a systematic search of scientific articles published between 2021 and 2025 using PubMed, ScienceDirect, and Google Scholar databases. The findings indicate that major challenges in health human resource management include limited financing, gaps in digital competence and literacy, high workload, inadequate digital infrastructure, data security and ethical issues, and weak collaboration among stakeholders. Strategies to address these challenges include sustained investment in digital health infrastructure, strengthening policies and regulatory frameworks, continuous education and training, curriculum development, implementation of ethical digital governance, and enhanced cross-sector collaboration. This review concludes that adaptive and innovative health human resource management plays a crucial role in supporting sustainable and effective digital health transformation in the context of global change.